Teaching Some Types of Phraseological Units in English Lessons (Eurasian Journal of Philology Science and Education, 2024)
There are two types of word combinations in the language: free word combination and fixed word combination. Fixed word combinations are also called phraseological combinations. Phraseological combinations are stable word combinations that do not change in composition and convey a figurative meaning as a whole. Phraseological combinations are readily available in the language. It is possible to replace some of them with one word. Words that make up phraseological combinations can be two or more. Phraseological compounds are part of a whole sentence without being divided into constituent parts. Phraseological combinations differ from free word combinations, so that while the words included in their composition are used in their true meaning, individual words in the composition of phraseological combinations lose their true meaning, together they express a certain figurative meaning. Unlike free phrases, fixed phrases do not have a dependent or a main part. They enter dictionaries. Phraseological combinations also have the feature of homonymy, synonymy and antonymy, and phraseological combinations include phraseological units, phraseologisms, phraseological compositions, idioms, collocation, paremia, proverb, quote etc. Studying English phraseological units expands learners' memory, allowing them to quickly and sufficiently select lexical units. This method, in turn, shapes the emotional expressiveness and expressiveness of speech. Searching for the equivalent of the analysed phraseological unit in the native language and explaining its meaning significantly develops translation skills and abilities. Scholars are also encouraged to work with phraseological dictionaries, which has the effect of expanding the vocabulary of the learners. The purpose of the research - the evolution of methodologies makes it possible to understand the place how to teach some types of phraseological units of teaching in English lessons and help with target language communication.Keywords: didactic, phraseological units, types, word combinations.